(3OQQ GdMcGe aj TQM ZQQ GdCMcGes - (3edG NSQh, eMeO Hf aQGehR Hf Ydj, J (B885 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CMce CMcGe GdTQY Gdbhje HeMce cJGHg CeG HYO aEf GdebOeGJ GdebQQI YfO Chdj GdCHUGQ aTQYJ aj TQMg hCSejJg OQQ GdCMcGes
(3BNQgG (B:s
(3Edi aSN GdMGce dCf GdhUj dh YRe Ydi JQc GdNUheI cGf aSNgG HefRdI GdEbGdI ajdRe GdhUjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 328s
(3eYLe GdeDdajf (B3 / 584s
(3cTa GdXfhf (B2 / 1199s
(3TPQGJ GdPgH (B7 / 342s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs